Global Epidemiology of Movement Disorders: Rare or Underdiagnosed? - O'Shea, Sarah A.; Shih, Ludy C. (Seminars in Neurology, 2023)
In this manuscript, we review the epidemiology of movement disorders including Parkinson's disease (PD), atypical parkinsonism, essential tremor, dystonia, functional movement disorders, tic disorders, chorea, and ataxias. We emphasize age-, sex-, and geography-based incidence and prevalence, as well as notable trends including the rising incidence and prevalence of PD. Given the growing global interest in refining clinical diagnostic skills in recognizing movement disorders, we highlight some key epidemiological findings that may be of interest to clinicians and health systems tasked with diagnosing and managing the health of patients with movement disorders.
Keywords: epidemiology; parkinsonism; dystonia; essential tremor; atypical parkinsonism; tic disorders; ataxia; chorea; Huntington's disease